Analisis Wacana Kritis Norman Fairclough; Representasi Kekerasan Seksual pada Laki-laki dalam Serial Baby Reindeer - Muhammad Al Kautsar; Chatarina Heny Dwi Surwati (Universitas Sebelas Maret (UNS), 2026)
This study aims to analyze how sexual violence against men is represented in the series Baby Reindeer using Norman Fairclough’s Critical Discourse Analysis (CDA) approach. Sexual violence toward men remains a socially taboo topic and is rarely explored in mainstream media discourse. Therefore, this research seeks to uncover the discursive constructions embedded within audio-visual media narratives. The series Baby Reindeer, based on the true story of Richard Gadd, was chosen due to its complex portrayal of male trauma resulting from sexual violence. This research employs a descriptive qualitative method, utilizing Fairclough’s three-dimensional analysis framework: textual analysis (micro), discourse practice (meso), and socio-cultural practice (macro). The data consists of selected scenes from the series that portray sexual violence—both physical, verbal, and psychological—which are analyzed through the lenses of representation theory and queer theory. The findings reveal that sexual violence against men in Baby Reindeer is represented through character complexity, visual symbolism, and dialogues that challenge hegemonic masculinity. The series subtly critiques patriarchal structures that often silence male victims and highlights how power relations and gender identity shape social meanings. Thus, Baby Reindeer not only illustrates personal trauma but also invites broader reflection on the societal discourse surrounding sexual violence and gender dynamics.